Quantum Physics Based Analytical Modeling of Drain Current of Single Electron Transistor with Island Made of Zigzag-Tungsten Disulfide Nanoribbon - Bera, Milan Kumar (East European Journal of Physics, 2020)
Among many emerging nanoelectronic devices, single-electron transistor (SET) is one of the frontier device architectures that can offer high operating speed at an ultra-low power consumption. It exploits controlled electron tunneling to amplify current and retains its scalability even on an atomic scale. A new island based SET device architecture is proposed which is made of monolayer tungsten disulfide nanoribbon (WS2 NR) in zigzag pattern. The quantum physics based analytical model is developed in order to investigate the tunnelling drain current flowing through the proposed WS2 NR SET. It has been observed from the simulation study that the device current did not struggle in the coulomb blockade region whereas outside this region drain current value gradually decreases for longer nanoribbon likely due to formation of wider potential well in the island regime which helps to drop the rate of tunnelling electrons.